Self-assembled spheres, flowers, and fibers from the same backbone and similar side chains - Singh, Anup Kumar; Krishnamoorthy, Kothandam (Langmuir, 2017)
Rylene imides (Ms) self-assemble into various nanostructures. Often, the synthesis of unsymmetrical RIs (URIs) is required to achieve nanostructures. However, the synthesis of URIs is nontrivial. Thus, a structurally similar alternative is desirable. iso-Indigo (i-indigo) has a pi core and lactam rings that are structurally similar to the RIs. Unsymmetrical iso-indigo (i-indigo) can be easily synthesized by condensing oxindole and isatin. We have synthesized a series of unsymmetrical i-indigo molecules. In these molecules, the pi-pi interaction, hydrogen bonding, and van der Waals interactions are in operation. Because of these, the molecules self-assemble into spheres, fibers, and dahlia flower morphologies. If the hydrogen bonding interaction is disrupted, then all of them form fibers. Control experiments indicate that the complete absence of hydrogen bonding is deleterious to self-assembly. We also show that the lower analogs of i-indigo are not sufficient to form self-assembled nanostructures.

Nanoporous reduced graphene oxide and polymer composites as efficient counter electrodes in dye-sensitized solar cells - Sudhakar, Vediappan; Singh, Anup Kumar; Chini, Mrinmoy Kumar (ACS Applied Electronic Materials, 2020)
The introduction of an efficient and precious platinum (Pt) free counter electrode (CE) for dye-sensitized solar cells (DSSCs) is an important aspect to address. In this report, we have employed nanoporous reduced graphene oxide (PG) containing PEDOT:PSS-PG composite on FTO substrate as CEs, which have shown excellent diffusion of I-3(-), remarkable photocatalytic activity, and better device performance along with desired stability. The investigated cathode material has been prepared by mixing PGs and highly conducting PEDOT:PSS. Experimental measurements and analyses such as electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV), and so on indicate that PEDOT:PSS-PG is a promising cathode material for a Pt-free CE in DSSCs. EIS indicates that the PEDOT:PSS-PGs have lower interfacial charge-transfer resistance because of their high electrical conductivity and superior electrocatalytic activity. The achieved photoconversion efficiency (eta) of a DSSC employing the Pt-free PEDOT:PSS-PG/FTO CE is 9.57%, which is found to be comparable to that of Pt/FTO CE based DSSC (9.64%) under a simulated solar light illumination of 100 mW/cm(2).
Keywords: counter electrode; Dye-sensitized solar cells; electrocatalytic activity; PEDOT:PSS; Reduced graphene oxide

Highly efficient method of utilizing waste silica hazards - Singh, Anup Kumar; Sudhakar, Vediappan (Process Safety and Environmental Protection, 2021)
Silica gels are the significant commodity solid waste produced by organic laboratories and pharmaceutic industries. Although use of silica gels is continuously growing, the proper methods of re-utilizing silica waste are yet limited. Hence, it demands a non-traditional approach to transform these silica waste into some other useful products apart from using them as a well-known road construction materials. Hereby, we report the fabrication and applications of monolithic polymer-silica composites by ice-templating technique from laboratory waste silica-gels, using green approach. To the best of our knowledge, the fabrication of organic-inorganic hybrid sponges from the particles of hundreds of microns is not reported to date. Scaffolds S-60, S-120, S-180, and S-300, were prepared from laboratory discarded silica gels. The morphological, physicochemical, flame-retardant, and liquid absorbent properties of these self-standing scaffolds were analyzed. Results showed that the incorporation of silica particles in the scaffolds turned them into a flame-retardant sponge. These properties make the sponges ideal for making non-flammable cushions, applicable in automobiles, aircrafts, chemical laboratories, hospitals, and other areas of applications. Due to the large porous structures, these scaffolds possess excellent absorption properties and may absorb almost every kind of liquid ranging from oils to acids. Therefore, these scaffolds are also a remarkable absorber for oils and hazardous liquids spillage, such as acids, and can be used as foam for chemical packing applications. (C) 2021 Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Acid absorber; Flame-retardant; Ice-templating; Laboratory silica waste; scaffolds

i-Indigo-based self-assembled microparticles and their conversion to nanoparticles - Singh, Anup Kumar; Swain, Gitanjali (ChemistrySelect, 2023)
Microscopic particles (MPs) are used to scatter and reflect UV light. It is well established that inorganic MPs such as TiO2 and ZnO produce carcinogens. Therefore, organic MPs are explored for UV absorption. Conjugated chromophores with differing lipophilicity usually self-assemble into nanoscopic structures. In our previous experiments, unsymmetrical i-Indigo was found to self-assemble into 500 nm particles. We hypothesized that the size of the self-assembled particles can be increased by increasing the lipophilicity difference between the side chains. Toward this objective, we have chosen the i-Indigo core with TEG and alkyl chains as side chains. As a result, the i-Indigo molecules were found to self-assemble into 3 & mu; spheres in solution. By substituting side chains with different lipophilicity, i-Indigo microparticles with the size of 5 & mu; are prepared. A careful analysis showed that the spheres are similar to a soccer ball, and they deflate upon drying on the substrate surface. The judiciously chosen side chain binds with a metal-ion (Cs+) and forms nanoscopic assemblies. After Cs+ binding, the size of the particles is decreased drastically to 100 nm. The simple addition of ions converts microscopic assemblies into nanoscopic assemblies.
Keywords: Isoindigo; microparticles; Nanoparticles; Self-assembly; UV absorber

Solvatochromism and side chain effects on the morphological behavior of bodipy-alt-i-Indigo copolymers - Singh, Anup Kumar; Swain, Gitanjali; Birajdar, Sarika (New Journal of Chemistry, 2024)
Among the factors that govern the self-assembly of a molecular system, side chains and solvent polarity play crucial roles in the morphological alteration of small molecules in solutions. Although the effect of side chains on the self-assembly of small molecules has been studied well, reports on their importance in the aggregation behavior of polymers are limited. Investigating whether a minor change in the side chain produce any significant impact on the morphology of the polymer in solution is of great research interest. Towards the end goal, to alter the morphology of polymers and to know the impact of the side chains on the self-assembly properties of the conjugated polymers, two BODIPY-i-Indigo alternating copolymers, P1 [poly(BDP12-alt-iI)] and P2 [poly(BDPE-alt-iI)], were synthesized, and their aggregation behavior was explored in various solvents. Both the copolymers, P1 and P2, exhibited narrow PDI values of 1.16 and 1.45, respectively. Although their cores are the same, P1 showed a thin film morphology, while P2 displayed a porous morphology (approximately 557 nm) in chloroform. On changing the solvent, P1 showed a porous morphology in a 50% THF-CHCl3 mixture. However, in P2, the pores were reduced to extremely small sizes in the 50% THF-CHCl3 mixture. This work demonstrates that even a minimal change in the side chains of copolymers and polarity differences between solvents can produce a drastic morphological effect.